2009
DOI: 10.1055/s-0039-1697433
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Patients with Trigeminal Neuralgia Referred to Neurosurgery

Abstract: Objectives: To investigate the clinical characteristics of patients with trigeminal neuralgia referred to surgery in a center of reference.Methods: We evaluated the general characteristics of 395 patients with trigeminal neuralgia referred to neurosurgery as treatment. They corresponded to 2 samples of 1984 and 2004. The EDOFHC protocol (Orofacial Pain Questionnaire) and the medical profile were used.Results: In the first study (1984), with 290 patients, the higher prevalence was: women (57.3%), white (95.5%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 19 publications
5
14
2
4
Order By: Relevance
“…This is compared with a prevalence rate of only 58/100,000 (0.058%) in the US population overall. 44 We noted that the proportion of women was slightly higher in this study than for the TN population reported in other literature 71.8% vs ~60% 6,8,45 , respectively) and the authors' own practices, most likely due to the fact that women are more likely to access care and typically live longer than men.…”
Section: Opioidscontrasting
confidence: 54%
“…This is compared with a prevalence rate of only 58/100,000 (0.058%) in the US population overall. 44 We noted that the proportion of women was slightly higher in this study than for the TN population reported in other literature 71.8% vs ~60% 6,8,45 , respectively) and the authors' own practices, most likely due to the fact that women are more likely to access care and typically live longer than men.…”
Section: Opioidscontrasting
confidence: 54%
“…Only 1 (0.47%) patient presented with bilateral affliction. This finding is similar in those of other studies as well (Katusic et al, ; Loh et al, ; Siqueira, Teixeira, & Siqueira, ). Overall, RV3 (35.19%) was the most frequently affected division, followed by LV3 (25.93%), RV2 (14.35%) and LV2 (12.04%).…”
Section: Discussionsupporting
confidence: 93%
“…Very few studies have appeared in the literature that have explored the temporal relationship between hypertension and TN. Two of these studies have reported a positive association between TN and hypertension, while 1 study was unable to show a significant association [4][5][6]. Here we describe the case of a patient who presented TN attacks precipitated by unstable blood hypertension.…”
Section: Introductionmentioning
confidence: 71%